Resource Allocation in Cloud Computing with General Classification Time and Exponential Service (G/M/s) (International Journal of Engineering and Computer Science, 2014)
In this article we considered a Cloud Computing Network (CCN) with four nodes, classifier, SaaS, PaaS and IaaS. The classifier node serve as agent for the Service Level Agreement (SLA). It is a routing server which takes a random time which is independent identically and distributed. The other service stations took an exponentially distributed service time. Thus the CCN became a Network of G/M/s queues. The G/M/s type queue is justified because the arrival of service request to CCNs are in general not follow Poisson Process System perform measures are obtained to compute the total expected cost for the CCN.